Sewage sludge as potential resource for the production of cellulase: statistical optimization of media constituent of sludge - Drani , Afifah; Alam, Md. Zahangir; Muyibi, Suleyman Aremu (2009)
An optimization based on statistical design method was employed to optimize the media constituents for the cellulase production from sewage sludge through liquid state bioconversion (LSB) by filamentous fungus Trichoderma reesei RUT C-30. The statistical analysis of experimental result showed that the optimum media constituent for cellulase production using sewage sludge as the major substrate, containing 1.5% cellulose and 0.5% peptone, supplemented with 0.25% KH2PO4, 0.2% tween 80, and 0.03% MgSO4 gave the maximum cellulase activity of 21.33 U/ml (CMCase activity). Analysis of variance (ANOVA) showed a high coefficient of determination (R2) of 0.92 with very low probability value (p < 0.0001) for the developed model. The present model is a good prediction of the experimental results and it is highly significant.